1999
DOI: 10.1620/tjem.188.119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mandibular Advancement Splint on Psycho-Intellectual Derangements in Patients with Sleep Apnea Syndrome.

Abstract: The mandibular advancement splint (MAS) was recently introduced for the management of sleep apnea syndrome (SAS), although its effects on psycho-intellectual functions have not been elucidated yet. We examined psycho-intellectual function before and after treatment with MAS in patients with SAS. Twenty patients with SAS underwent psycho-intellectual function testing before and after treatment with MAS for 3 to 4 weeks. The apnea index significantly decreased from 19.0+/-15.6 to 2.4+/-1.9. The state anxiety sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
1
8
0
1
Order By: Relevance
“…Moreover, the amount of mandibular advancement by an OA has been determined in the light of the best balance between clinical indications and contraindications (42,48). Only one study has previously revealed that mandibular advancement with an OA significantly reduces clinical symptoms and improves cognitive function (43). Based on the findings in the present study, it may be possible to specifically determine the most efficient mandibular position by referring to the decrease in brain activation triggered by respiratory loading.…”
Section: Discussionsupporting
confidence: 51%
“…Moreover, the amount of mandibular advancement by an OA has been determined in the light of the best balance between clinical indications and contraindications (42,48). Only one study has previously revealed that mandibular advancement with an OA significantly reduces clinical symptoms and improves cognitive function (43). Based on the findings in the present study, it may be possible to specifically determine the most efficient mandibular position by referring to the decrease in brain activation triggered by respiratory loading.…”
Section: Discussionsupporting
confidence: 51%
“…Alternative treatments for OSA were explored. One study involved mandibular advancement splinting (Nambu et al, 1999), and two others involved surgical intervention by way of extended uvulopalatal flap (Li et al, 2004) and radiofrequency tissue ablation (Uloza et al, 2009). All three of these studies involving alternative interventions resulted in statistically significant decreases in anxiety levels.…”
Section: Resultsmentioning
confidence: 99%
“…Motivational strategies, referred to as motivational enhancement therapy for CPAP (ME-CPAP), have been developed to improve CPAP compliance (Aloia et al, 2004). Alternative interventional strategies include mandibular advancement splinting (Nambu, Nagasaka, Fujita, Hamada, & Fukuoka, 1999), and surgical dilation of the upper airway by way of extended uvulopalatal flap (Li et al, 2004) or radiofrequency tissue ablation (Uloza, Balsevicius, Sakalauskas, Miliauskas, & Zemaitiene, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A selected group of patients was recruited in 34 out of 55 studies (21–54). In 21 studies (55–75) the patient sample was drawn from consecutive series.…”
Section: Resultsmentioning
confidence: 99%
“…The mean severity of OSAS ranged from 10 to 99 apneas and hypopneas per hour (median: 48 apneas and hypopneas per hour), and the standard deviations varied widely. One study (42) reported the range and the median of AHI, one study (59) specified severity using the desaturation index indicating ≥4% decrease in minimum oxygen saturation at least five times per hour or at least 30 saturations during 7 h sleep, and one study (31) using the apnea index indicating the frequency of apneas per hour of sleep and apneic episodes per night. In two studies (34, 58) severity was reported categorically (mild, moderate, severe) without specifying the mean number of apneas and hypopneas per hour.…”
Section: Resultsmentioning
confidence: 99%